ANALYSIS OF THE CURRENT STATUS OF THE THEORY AND PRACTICE OF ASSESSING THE RELIABILITY OF SOFTWARE OF AUTOMATED INFORMATION AND CONTROL SYSTEMS - Yusupbekov N.R.; Gulyamov Sh. M.; Mirzaev D.A.; Kuziyev Z.J. (Galaxy International Interdisciplinary Research Journal, 2022)
The relevance and relevance of the problem of increasing the reliability of assessing the reliability indicators of the operation of information and control systems software at different stages of their life cycle through the use of adequate models, methods and analysis tools is shown. An analytical analysis of known approaches to assessing and predicting the reliability indicators of computer systems software has been carried out, their advantages and disadvantages have been established, which will make it possible to determine the reserves for increasing their reliability when evaluating modern complex and multicomponent software.